Pemberdayaan Trash Home Creative (THC) dalam Mewujudkan Masyarakat Berkelanjutan di Desa Desa Lumahan Kecamatan Senyerang, Kabupaten Tanjung Jabung Barat - Junaidi; Hastuti, Dwi; Parmadi; Hardiani; Achmad, Erni; Nurjanah, Rahma (Studium: Jurnal Pengabdian Kepada Masyarakat, 2024)
Empowerment of Trash Home Creative (THC) is an effort to realize a sustainable society that is not only important locally but also has global implications in reducing plastic waste and promoting environmental awareness. The urgency of this service lies in the escalation of the plastic waste problem that threatens the environment and public health. THC offers an innovative solution by converting plastic waste into creative and high-value goods, while creating economic opportunities for rural communities. The main objective of this service is to increase the capacity and independence of the community in managing plastic waste through THC. Through training, mentoring, and skills development, it is hoped that the community can understand environmental values, reduce environmental pollution, and increase their income through the sale of THC products. The targeted outputs are an increase in the number of residents involved in THC activities, an increase in the production of creative goods from plastic waste, and the adoption of environmentally friendly practices at the household level. In addition, it is hoped that a network of cooperation will be formed between THC and related parties such as local governments, non-governmental organizations, and the private sector to support the sustainability of this service. Furthermore, the outputs of this service activity will be published in the form of articles, videos and activity reports.